A rare complication of neonatal central venous access. Issue 1 (1st January 2002) - Baker, J; Imong, S
Abstract : Total parenteral nutrition is often necessary for the survival of neonates, but obtaining central venous access can be very difficult. A case is reported in which malpositioning of a 27 gauge central venous catheter resulted in the misdiagnosis of necrotising enterocolitis and hypoglycaemia.